Brain Death: The United Kingdom Perspective - Smith, Martin (Seminars in Neurology, 2015)
The United Kingdom (UK) has incorporated a brainstem formulation into its brain death criteria since the first guidelines were published in 1976. A clinical diagnosis incorporating three sequential but interdependent steps is sufficient for the determination of brain death in the UK. There must be no doubt that the patient's comatose condition is due to irreversible brain damage of known etiology, and potentially reversible causes of coma and apnea, such as drug effects, metabolic or endocrine disturbances, or hypothermia, must be excluded. A clinical examination of brainstem reflexes and an apnea test is then undertaken. Confirmatory tests are not required in the UK, but may be useful to reduce any element of uncertainty or minimize the period of observation prior to the diagnosis of brainstem death if the preconditions for clinical testing are not met, or if a comprehensive neurologic examination is not possible. Brainstem death must be diagnosed by two doctors who must be present at each of the two sets of clinical tests that are required to determine death. Although death is not confirmed until the second test has been completed, the legal time of death is when the first test confirms the absence of brainstem reflexes.
Keywords: brain death; brainstem death; United Kingdom